Louise Trapeze did NOT lose the juggling chickens - Ostow, Micol (Random House, 2016)
Seven-year-old Louise, who performs in a trapeze act with her mother and father, finally gets an important job at the circus, but when things go wrong she wonders if she is really ready for new responsibilities.